2022
DOI: 10.2174/0929867329666211221153719
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fyn Kinase Inhibitors in Switching Neuroinflammatory Pathways

Abstract: Fyn kinase is a member of the Src non-receptor tyrosine kinase family. Fyn is involved in multiple signaling pathways extending from cell proliferation and differentiation to cell adhesion and cell motility, and it has been found to be overexpressed in various types of cancers. In the central nervous system, Fyn exerts several different functions such as axon–glial signal transduction, oligodendrocyte maturation and myelination, and it is implicated in neuroinflammatory processes. Based on these premises, Fyn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…We confirmed that FYN was targeted by miR‐876‐5p. FYN plays an essential role in diverse cellular processes 28,29 . In addition, previous studies showed that FYN served as a tumor accelerator in multiple cancers 17,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that FYN was targeted by miR‐876‐5p. FYN plays an essential role in diverse cellular processes 28,29 . In addition, previous studies showed that FYN served as a tumor accelerator in multiple cancers 17,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of E6 and E7 resulted in the detection of many DEGs using RNA-seq and RT-qPCR. Fourteen of these hub genes were linked to cell adhesion ( Chute, 2006 ; Teicher and Fricker, 2010 ; Paolillo and Schinelli, 2019 ; Marotta et al, 2021 ), leukocyte–endothelial migration ( Yakovlev et al, 2019 ; Morein et al, 2020 ; Yan et al, 2021 ), stem cell signaling ( Davidson et al, 2007 ; Bijlmakers, 2009 ), and epithelial–mesenchymal transition ( Pastushenko et al, 2021 ; Wang et al, 2021 ). Based on these experimental and bioinformatics analyses, we hypothesized that HPV16 E6 and E7 signaling causes differential mRNA expression through direct or indirect mRNA pathways that regulate cell adhesion and chemokine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, its potential as a target for Alzheimer's disease and cancer has been highlighted (Sil and Ghosh., 2016;Pu et al, 2021). FYN, a tyrosine kinase, plays a signi cant role in neuroin ammatory processes, cell proliferation, differentiation, and adhesion, and its expression has been reported in various cancer types (Marotta et al, 2022;Saminathan et al, 2020;Elias et al, 2015).…”
Section: Network Pharmacology and Molecular Dockingmentioning
confidence: 99%